(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
Bibliometrics is a field of research that quantitatively analyzes bibliographic material. To this end, this article proposes a bibliometric analysis of the structuring of the problem for decision-making between 1980 and 2019, using the Web of Science database to collect scientific information. The objective of this research is to show bibliometric indicators including the total number of publications and citations, and h-index, as well as authors, countries, universities, sources and categories. The results show the relevance of the study topic, which increased in 1990, with 2018 and 2019 being the years with the greatest scientific production. Likewise, the United States and London are the countries that have the greatest production of documents on the subject and are key in the network of collaborators. The article may be useful for researchers and students who want to delve deeper into the topic, providing help to build a solid theoretical framework. Vosviewer software was used as a tool to build and visualize biliometric networks.